Cakupan pemeriksaan ibu hamil terhadap pemberian tablet zat besi - M.Lukman Arsyad, Ibrahim DP (Berita Kedokteran Masyarakat (BKM), 2005)
Background: In year 2005, the fifth year of autonomy, with the objective is to rise community welfare through equity of health service and close health facilities in the community in Bulukumba regency. The problem of this research is the coverage of basic health facilities for community in otonomics era (phase) that is still not known in facts. Objective: To measure coverage of pregnancy attendance with Ferro tablet and duration drink with Ferro tablets as equal with Health Service Standard (SPM). Method: The method of this study is observation ("cross sectional study") with rapid survey method and the processing of data using Epi Program Sixth (Epi6) version for Windows. Recording and reporting of Health Centre System (SP2TP) described the coverage of K-4 approximately 52,45% and the coverage of Ferro Tablets approximately 7,14%. Result: The result of this study showed K-4 ( the fourth consultation session) approximately 72,86% and the coverage of Ferro tablets approximately 53,33%, while the the coverage of Ferro tablets approximately 64,29% which are the same with the inspection of height of the fundus. Keywords: antenatal and Ferro tablets